ANALISIS STRUKTURAL TERHADAP CERITA RAKYAT LAU KAWAR SASTRA LISAN BATAK KARO - Pincawan, Gebry Ariel; Priyadi, Antonius Totok; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to determine the structure or intrinsic elements of the Lau Kawar folklore from Naman Teran District, Karo Regency. The research method used is descriptive with a qualitative research form. The data sources for this research are Mr. Sumardi, Mr. Kohar, and Mr. Rekam Pincawan and the data is a structure in the form of quotations of words, phrases, sentences and paragraphs. The results of this study are first: the theme contained in the Lau Kawar folklore is disappointment. Second: there are twelve settings consisting of three place settings, three time settings, five atmosphere settings, and one social setting. Third: the message contained in the Lau Kawar folklore is that you should never be disobedient to your parents. Fourth, the characters from the Lau Kawar folklore are one central character and four additional characters consisting of three additional characters and one background character. In terms of character, there are five characters consisting of five characters. Fifth: there are five parts to the plot stages, namely exposure, initiation, rise, climax, and completion. Sixth: implementation of the oral literature "Lau Kawar" as Indonesian language learning material in high school